An Industrial systems design study on Camel Appliances Mfg. Corp. - Dela Cruz, Ma. Alesandra K.; Gangoso, Cesar K. III; Ngkaion, Evette C.; Tan Afuan, Elaine C. (College of Engineering, 2001)
The principal objective of this study is to evaluate and improve the supply chain of Camel Appliances Manufacturing Corporation (CAMC). The study is divided into two major parts. In part I, the supply chain components (purchasing, inventory management, manufacturing, distribution management and customer service relations) are extensively documented. The organizational structures, policies, strategies, processes and performance measures of these supply chain components are discussed in detail. In part II, the SAPADAPPA framework was employed to analyze and evaluate the current system. Using the SAPADAPPA approach, six problems were identified. These problems were traced to five root causes using an Ishikawa and Streamline analysis. Then, alternatives were generated to address these problem causes. The best alternative was chosen using a criteria evaluation matrix. Finally, recommendations are summarized and an implementation program is proposed.